Optimization of pulse sequences in ultrafast magnetic resonance imaging for the diagnosis of acute abdominal pain caused by gastrointestinal disease - Inoue, Akitoshi; Furukawa, Akira; Nitta, Norihisa; Takaki, Kai; Ohta, Shinichi; Murata, Kiyoshi (Acta radiologica open, 2020)
Background Magnetic resonance imaging (MRI) is widely used to diagnose acute abdominal pain; however, it remains unclear which pulse sequence has priority in acute abdominal pain. Purpose To investigate the diagnostic accuracy of MRI and to assess the conspicuity of each pulse sequence for the diagnosis of acute abdominal pain due to gastrointestinal diseases Material and Methods We retrospectively enrolled 60 patients with acute abdominal pain who underwent MRI for axial and coronal T2-weighted (T2W) imaging, fat-suppressed (FS)-T2W imaging, and true-fast imaging with steady-state precession (True-FISP) and axial T1-weighted (T1W) imaging and investigated the diagnosis with endoscopy, surgery, histopathology, computed tomography, and clinical follow-up as standard references. Two radiologists determined the diagnosis with MRI and rated scores of the respective sequences in assessing intraluminal, intramural, and extramural abnormality using a 5-point scale after one month. Diagnostic accuracy was calculated and scores were compared by Wilcoxon-signed rank test with Bonferroni correction. Results Diagnostic accuracy was 90.0% and 93.3% for readers 1 and 2, respectively. Regarding intraluminal abnormality, T2W, FS-T2W, and True-FISP imaging were superior to T1W imaging in both readers. FS-T2W imaging was superior to True-FISP in reader 2 (P < 0.0083). For intramural findings, there was no significant difference in reader 1, whereas T2W, FS-T2W, and True-FISP imaging were superior to T1W imaging in reader 2 (P < 0.0083). For extramural findings, FS-T2W imaging was superior to T2W, T1W, and True-FISP imaging in both readers (P < 0.0083). Conclusion T2W and FS-T2W imaging are pivotal pulse sequences and should be obtained before T1W and True-FISP imaging.